Efficiency characteristics for changes in amplitude and power factor of diode‐clamped linear amplifier unequally divided voltage power supply. Issue 3 (26th August 2022) - Haruna, Junnosuke; Matano, Yusuke; Funato, Hirohito
Abstract: A diode‐clamped linear amplifier (DCLA) is proposed to realize low electromagnetic interference (EMI) caused by switching operations. A new concept of the DCLA, namely the higher efficiency unequally divided voltage power supply DCLA (DCLA‐UeDV), is proposed. In previous studies, the optimal voltage ratio was derived, and a 1.7% points improvement in efficiency was realized for a rated unity power factor load. However, it has not been examined whether the conversion efficiency can be improved, except during the rated operation. In this study, operation of the DCLA is analyzed for changes in the amplitude of the output voltage and load power factor. Then, the advantageous operating region of the DCLA‐UeDV against DCLA‐eDV is clarified.